Analysis of the influence of the curvature, сonstriction of S-chaped channel and flight conditions on the efficiency of the bucket inlet device - Oleg Zhornik; Ihor Kravchenko; Mykhailo Mitrakhovych; Ekaterina Balalaieva (Авіаційно-космічна техніка та технологія, 2022)
When creating a modern aircraft, the principle of optimal integration of the power plant and the aircraft is used to ensure the maximum target function, determined by its functional purpose. The specific fuel consumption and specific thrust of the power plant depend significantly on the loss of the total air pressure in the inlet device, which is characterized by the total recovery factor. The change in pressure along the diameter of the propfan affects the efficiency of the inlet of the power plant. When using the inlet ring device, its efficiency decreases, due to low pressure in the area of the root part of the propfan blades. The use of a bucket inlet allows air to be supplied to the channel from the area located near the middle part of the blade height and this is the main factor influencing the reduction of pressure losses in the air supply channel. When using a bucket inlet, curvature and constriction are important factors influencing the effectiveness of S-channels. The influence of the curvature of the S-shaped channel on the total pressure recovery coefficient at a constant value of its narrowing is studied in this work. The study S-shaped channel in its geometric parameters is equivalent to the channel of the annular inlet device of a power plant with a turbofan engine. The total pressure recovery coefficient of an S-shaped channel is calculated from the flow parameters in the sections of the S-shaped channel by solving the Navier-Stokes equations using the Florian Menter two-layer turbulence model (SST Transitional No. 4 Gamma Theta) and the combined finite element model at the entrance to the channel and in the channel itself - hexahedral, at the exit tetrahedral. An analysis of the dependence of the total pressure recovery coefficient of the S-shaped channel on the M number and the channel curvature shows that, up to a curvature of 0.002, the total pressure recovery coefficient is not significantly affected. A further increase in the channel curvature has a significant effect on the change in the total pressure recovery coefficient, which is associated with flow separation and losses from the vortex formation.